Saccharomyces fragilis IZ 275 IN CHEESE WHEY CELL PERMEABILIZATION USING DIFFERENT ORGANIC SOLVENTS (Research, Society and Development, 2020)
The aim of this study was to verify the efficacy of different organic solvents, in the permeabilization of Saccharomyces fragilis IZ 275, by using a Central Composite Rotational Design (CCRD) 23 and Response Surface Methodology (RSM). Furthermore, we aimed to evaluate the effectiveness of the permeabilization process by monitoring lactose hydrolysis and obtaining images of non-permeabilized and permeabilized cells by Scanning Electron Microscopy (SEM). The yeast S. fragilis IZ 275 was grown in a fermentation medium composed of cheese whey, and the permeabilized cells was estimated by β-galactosidase activity. The response surface methodology was used as it is an efficient tool to optimize the permeabilization process as well as to identify the organic solvent which was most effective for this process. Our results show that the concentration and type of organic solvent, as well as permeabilization temperature and time influence the cells permeabilization process.. Considering the experimental results, the best conditions when using chloroform are a concentration of 4 % at 25 ºC during 20 min with 81.03 % lactose hydrolysis. In this study, we found that the use of ethanol for cellular permeabilization  lead to obtaining β-galactosidase enzyme, a process which can be used in a large scale by the food industry, being a cheaper and more environmentally safe way of obtaining this enzyme.